Work context and drinking behavior in the French public service: a qualitative study - du Sartz de Vigneulles, Benjamin; Carrouel, Florence; Roucoux, Guillaume; Michel, Christian; Massoubre, Catherine; Motyka, Geneviève; Verot, Elise; Dussart, Claude (Frontiers in Public Health, 2024)
Alcohol use disorders (AUD) are a major public health problem. Among the working population, alcohol is the most frequently used psychoactive substance, as well as the most inappropriately used. Alcohol consumption reduces the worker's psychophysical integrity, leads to an increase in inappropriate behavior, accidents and injuries, and affects the safety and health of other workers. Thus, the workplace must play an essential role in prevention. Particularly in France, in the civil service, a specific professional sector made up of many professionals exposed to stress, the prevention of AUD must play an essential role. The objective of this study was to describe the framework of alcohol consumption in the French public service in order to understand the sources of alcohol consumption behaviors and to identify the prevention measures to be implemented, in order to reduce the risk of transition to an alcohol use disorder. This descriptive qualitative study was based on focus groups. Sampling was purposive and data saturation was verified. Coding was "in vivo", descriptive and pattern-oriented. Analysis was inductive thematic, and the COREQ guidelines were followed. Firstly, the presence of alcohol in the workplace has been characterized by a before-and-after a prohibition law, and by the revelation of mechanisms for avoiding the ban. Then, the three main determinants for alcohol use disorders were: society, work and personal factors. Lastly, the prevention initiatives identified must be based on both collective and individual approaches. They must be encouraged by the hierarchy, include screening, accompaniment to care, and take into account both work in the workplace and work at home.The fight against work-related alcohol use disorders must be part of the corporate culture. Preventing alcohol-related disorders among civil servants will help fight the burden of non-communicable diseases.